Physical activity habits and their relationship with sociodemographic factors in Chilean adolescents - Fuentealba-Urra, Sergio; Rubio, Andrés; Flores-Rivera, Carol; González-Carrasco, Mónica; Oyanedel, Juan Carlos; Castillo-Quezada, Humberto; Céspedes-Carreño, Cristian; Pacheco-Carrillo, Jaime (Frontiers in Psychology, 2022)
Physical activity plays an important role in the well-being and development of adolescents. Physical activity habits expressed in terms of frequency and duration are consistently associated with sociodemographic factors such as age, gender, and socioeconomic status. However, there is less evidence of the relationship between the type and context of physical activity in adolescents. The aim of this article is to analyze physical activity habits and their relationship with sociodemographic factors in Chilean adolescents. The cross-sectional study consisted of 7,263 adolescents aged between 10 and 20 years old, students from both public and private schools in all regions of Chile. Physical activity habits were examined by means of a self-report questionnaire. The age groups were classified according to the three stages of adolescence (early: 10 to 13, middle: 14 to 16, and late: 17 to 20 years old). Socioeconomic level was established based on the school vulnerability index (SVI) of the school attended by each adolescent. In the study it was obvious to the level of physical activity for the adolescents was below the international recommendations. A statistically significant association can also be found between the sociodemographic factors studied and the physical activity habits reported by the young people. The multivariate regression analysis established that the risk of not achieving the physical activity recommendations was 2.8 times higher in females than in males, 2.4 times higher in the older age groups (14–16 and 17–20 years old) compared to the 10–13-year age range and 1.1 times in the medium and high vulnerability groups than in the low socioeconomic vulnerability group. These findings highlight the importance of considering all these factors holistically whenever designing programs or public policies that promote the development of healthy physical activity habits in adolescents.